Interior graphic standards - Binggeli, Corky (Hoboken, N.J. : Wiley, 2012)
'The student edition of Interior Graphic Standards, Second Edition, carefully selects content from the professional book that specifically pertains to students to cover critical information on interior architecture and design. Topics new to this edition include: residential design, exterior construction as it relates to interiors, sustainable materials, expanded coverage of equipment and furnishings, building information modeling (BIM), integrated project delivery (IPD), and virtual collaboration. A password-protected instructor web site includes pedagogical materials, suggested course schedules, essay exam questions, project requirements, lecture notes, presentations, and review questions'--
'The student edition of Interior Graphic Standards, Second Edition, carefully selects content from the professional book that specifically pertains to students. Topics new to this edition include: - Residential Design - Exterior construction as it relates to interiors - Sustainable Materials - Expanded coverage of equipment and furnishings - Building Information Modeling (BIM), Integrated Project Delivery (IPD), and Virtual Collaboration - New Interior typologies, such as residential, recreational, and fitness spaces'--
Preface. Section I. Design Principles and Process -- Chapter 1. Environmental and Behavioral Issues -- Chapter 2. Acoustical Principles -- Chapter 3. Accessible Design Basics -- Chapter 4. Sustainable Design Basics -- Chapter 5. Design Basics -- Section 2. Building Elements -- Chapter 6. Structure and Shell -- Chapter 7. Interior Construction -- Chapter 8. Equipment and Furnishings -- Chapter 9. Interior Project Types -- Appendix. Classical Interior Architectural Elements -- Glossary -- Index.
Machine generated contents note: Preface. Section I. Design Principles and Process. Chapter 1. Environmental and Behavioral Issues. Chapter 2. Acoustical Principles. Chapter 3. Accessible Design Basics. Chapter 4. Sustainable Design Basics. Chapter 5. Design Basics. Section 2. Building Elements. Chapter 6. Structure and Shell. Chapter 7. Interior Construction. Chapter 8. Equipment and Furnishings. Chapter 9. Interior Project Types. Appendix. Classical Interior Architectural Elements. Glossary. Index.
Includes index.
Keywords: Building -- Details -- Drawings; Building -- Details -- Drawings -- Standards